Blending effects of boron carbide and lanthanum(III) oxide reinforcements on the structural, physical, mechanical, and radiation shielding properties of 316L-stainless steel composites for nuclear applications - ALMisned, Ghada; Yayla, Nihal; Albayrak, M. Gokhan; Guiler, Omer; Sen Baykal, Duygu; Alkarrani, Hessa; Tekin, H. O. (Pergamon-Elsevier Science Ltd, 2025)
Four composite samples were fabricated, maintaining 10 % B4C and varying La2O3 content from 0 % to 20 %. Xray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray Spectroscopy (EDX) analyses confirmed the successful incorporation of reinforcements, preserving the austenitic structure of 316L-SS. Elastic modulus calculations revealed a gradual reduction from 225.0 GPa to 215.0 GPa with increasing La2O3 due to clustering and reduced homogeneity. Gamma-ray shielding properties demonstrated significant improvements, particularly at low and intermediate photon energies, with Sample 4 with 20 % La2O3 addition, achieving a 13.6 % higher linear attenuation coefficients (LAC) at 0.015 MeV. Neutron shielding highlighted Sample 4 as one of the most effective materials, outperforming conventional alloys. This study demonstrates the potential of 316L Stainless-Steel (316L-SS) + B4C + La2O3 composites as multifunctional materials for radiation-intensive applications, offering superior attenuation and structural stability. It can be concluded that optimization of reinforcement distribution would play an important role in balancing mechanical and shielding performance in next-generation nuclear materials.
Keywords: 316L stainless-steel; Boron carbide; Lanthanum(III) oxide; Nuclear radiation shielding